Handling Domestic Violence from the Perspective of Islamic Law and Positive Law in Indonesia - Iskandar, Iskandar; Diah Nurafifah; Muhammad Irsan; Hamdan Purnama; Shinta Azzahra Sudrajat; Didin Nurul Rosidin (Unifikasi: Jurnal Ilmu Hukum, 2025)
The increasing problem of domestic violence has triggered a conflict between the implementation of the Law on the Elimination of Domestic Violence and Islamic values. Differences in interpretation and patriarchal culture hinder law enforcement, making it difficult for victims to obtain adequate protection. Therefore, this study aims to examine the principles of justice, gender equality, and feminist theory using a normative legal method by comparing positive law and Islamic law, as well as a conceptual legislative approach. The data used include primary legal materials, namely the Law on the Elimination of Domestic Violence, the Qur'an, and Hadith, secondary legal materials, including literature and journals, as well as tertiary sources collected through a literature review and analyzed qualitatively. The results showed that domestic violence against women is a violation of human rights, currently recognized as a significant crime through the Law on the Elimination of Domestic Violence. This law provides legal protection for victims and sanctions for perpetrators. Gender-based violence rooted in patriarchal culture perpetuates social inequality and discrimination against women. Islam and feminism make significant contributions by emphasizing the values of equality, justice, and respect in domestic relationships. The synergy between positive law, religious values, and feminist theory can be a strategic step toward eliminating violence and creating a more inclusive society.